Surfactant effect of impurity sulphur in ductility dip cracking of a high-chromium nickel model alloy. (15th March 2021) - Rapetti, A.; Christien, F.; Tancret, F.; Todeschini, P.; Hendili, S.; Stodolna, J.
Abstract: The sensitivity to ductility dip cracking was measured in two model high chromium nickel alloys, with the same composition, apart from different sulphur contents. The newly developed Refusion Cracking Test was used, that consists in repetitive refusion lines conducted at the specimen surface. Grain boundary cracks develop in the heat affected zone near the refusion line. Cracking is much more pronounced in the sulphur-enriched alloy, which demonstrates a strong deleterious effect of sulphur. However post-mortem analyses using WDS and STEM-EDS revealed no segregation of sulphur at grain boundaries. In contrast, grain boundary fracture surfaces are covered with sulphur. This suggests a dynamic type of grain boundary embrittlement where sulphur acts as a surfactant, facilitating crack opening. Sulphur is efficiently provided to the crack tip as it propagates, due to accelerated diffusion by plastic deformation. This allows crack growth rates higher than 10 µm/s. Graphicala abstract: Image, graphical abstract